Physico-chemical Characteristics of Oil and Seed Residues of Bauhinia variegata and Bauhinia linnaei - Sarfraz Arain; Najma Memon; Muhammad T. Rajput; Syed T. H. Sherazi; Muhammad I. Bhanger; Sarfaraz A. Mahesar (Pakistan Journal of Analytical & Environmental Chemistry, 2012)
Physico-chemical characteristics of two Bauhinia seed varieties (B. variegata and B. linnaei), were evaluated for commercial exploration. Physico-chemical characteristics of the oils for both varieties were demonstrated and mean values found to be refractive index (40 °C) 1.4589 and 1.4588, peroxide value 1.9 and 2.4 (meq O2 / kg of oil), iodine value 84.5 and 92.2 (g of I2/100g of oil), saponification number 191.3 and 195.5 (mg of KOH /g of oil), free fatty acids 0.6% and 0.9%, unsaponifiable matter 0.9% and 1.2% and color (1 in. cell), 2.2-2.9R + 30.0-25.0Y, respectively. Linoleic 42.1 and 45.8 %, oleic 13.4 and 12.6%, stearic 17.5 and 18.8% and palmitic 22.1 and 16.8% were the main fatty acids in the crude seed oils. Minor amounts of palmitoleic, margaric, linolenic, arachidic, behenic, eicosapentaenoic and nervonic acid were also identified. The composition of defatted seed residue of B. variegata and B. linnaei were found as: protein 41.9% and 38.6%, oil 18.0%, and 17.4% ash 4.8% and 4.2%, moisture 6.7% and 6.3%, fiber 6.9% and 7.3% and total carbohydrate 28.4% and 33.8%, respectively. Proximate and fatty acid composition of both Bauhinia varieties were found to be almost similar. It was concluded that Bauhinia seed is a rich source of linoleic acid and could be explored for commercial uses.